Curbing Free Speech: Strategic Lawsuits against Public Participation in India - Katrak, Malcolm (Christ University Law Journal, 2021)
There has been a sharp increase in the number of suits and legal notices threatening defamation. This substantial increase is due to the corporate companies aiming to stifle public discourse or bona fide criticisms. The apt term coined for defining these lawsuits is SLAPP (Strategic Lawsuits against Public Participation).Not only does this capture the causation, but also the consequences of these lawsuits. Curbing SLAPPs is essential, as it strikes at the root of democracy by not just affecting the defendant with frivolous claims, legal costs and hassles, but by also aiming at choking public discourse. This paper analyzes the issues relating to SLAPP suits and also the consequences of the same by examining various case laws. Thereafter, the author has suggested the need for Anti-SLAPP legislation and has also provided guidelines for formulation of the same.